Cohort profile: the Adverse Childhood Experiences cohort of the Malawi Longitudinal Study of Families and Health - Jere Behrman; James Mwera; Hans-Peter Kohler; Rachel Kidman; Yang (Tingting) Rui; Etienne Breton; Andrew Zulu (BMJ Open, 2024)
Purpose The Adverse Childhood Experiences (ACE) cohort of the Malawi Longitudinal Study of Families and Health (MLSFH-ACE) is a study of adolescents surveyed during 2017–2021. It provides an important opportunity to examine the longitudinal impact of ACEs on health and development across the early life course. The MLSFH-ACE cohort provides rich data on adolescents, their children and adult caregivers in a low-income, high-HIV-prevalence context in sub-Saharan Africa (SSA).Participants The MLSFH-ACE cohort is a population-based study of adolescents living in three districts in rural Malawi. Wave 1 enrolment took place in 2017–2018 and included 2061 adolescents aged 10–16 years and 1438 caregivers. Wave 2 took place in 2021 and included data on 1878 adolescents and 208 offspring. Survey instruments captured ACEs during childhood and adolescence, HIV-related behavioural risk, mental and physical health, cognitive development and education, intimate partner violence (IPV), marriage and aspirations, early transitions to adulthood and protective factors. Biological indicators included HIV, herpes simplex virus and anthropometric measurements.Findings to date Key findings include a high prevalence of ACEs among adolescents in Malawi, a low incidence of HIV and positive associations between ACE scores and composite HIV risk scores. There were also strong associations between ACEs and both IPV victimisation and perpetration.Future plans MLSFH-ACE data will be publicly released and will provide a wealth of information on ACEs and adolescent outcomes in low-income, HIV-endemic SSA contexts. Future expansions of the cohort are planned to capture data during early adulthood.